Ланцетоподібні наконечники стріл з Рухотина (урочище Корнешти) - Калініченко, Віталій; Пивоваров, Сергій (Чернівці, Видавництво "Прут", 2013)
In this article the authors introduce the scientific revolution and analyze the rarest arrowheads from Bukovіna namely lanceolate. Prove that they are of Scandinavian origin. The authors carried out a classification o f arrowheads of this type. Identified materials yield new data fi'om the previous inhabitants of the region VІІI-XI century A.D. military-political aspect.
Lanceolate arrowheads from Ruhotyn (Korneshty)
Ланцетовидные наконечники стрел из Рухотина (уроч. Корнешты)
Keywords: Буковина; Скандинавія; наконечники стріл; озброєння; типологія